Designing Internal Audit Rating for Evaluating The Implementation of Risk Management and Internal Control at PT Bank BNI Syariah (The Indonesian Journal of Business Administration, 2014)
Abstractâ€”Under Law 10 of 1998 on the Amendment of Act No. 7 of 1992 Article 29, every bank in Indonesia are required to have and implement a system of internal control in order to guarantee the implementation of the decision-making process in the management of the bank in accordance with the precautionary principle. Therefore, since the BNI Syariah spin off the Internal Audit Division (IAD) was formed in June 2010 for internal control function. IAD BNI Syariah Division has oversight directly and indirectly to all of these areas and produce a qualitative audit report. That why the audit report are not comparable either by the auditee or per audit period. In addition it is sometimes difficult to conclude the qualitative audit reports that will impact on decision making erroneous. This project aims to provide a model of the proposed Internal Audit Rating (IAR) as a tool to calculate the final measurement of the quantitative audit results. There are two main components of IAR which is assessment criteria and weighting of each of the criteria. In determining the major components of IAR, survey, observation and literature review are conducted to find the calculations model in accordance with the needs of BNI Syariah. Research conducted indicates that IAD Related parties need IAR for their stated objectives. Criteria and weights used in the calculation of the IAR is Risk Management (30%), Internal Control (25%), Auditee Performance (15%), Sharia Compliance (20% ) and Audit findings Follow-up (10%). Periodic review of the weights of each criterion is necessary in evaluating IAR.Â Keywords: Risk Management, Internal Control, Sharia Compliance, Auidtee Performance, Audit Findings Follow up.